Malnutrition during pandemic among home-nursed and community-dwelling elderly. - NGADIARTI, Iskari; MUNTIKAH, Muntikah; NURKOLIS, Fahrul; GUNAWAN, William Ben (Nutrición Clínica y Dietética Hospitalaria, 2022)
Background: The current COVID-19 pandemic has led to serious changes in the daily routine of people including the elderly. One of the most feared impacts is the increasing malnutrition among the elderly, which contributes to exacerbating public health problems. Objective: To evaluate the differences in nutritional status, the risk of malnutrition, and nutritional intake between the elderly receiving home nursing and community-dwelling elderly during the COVID 19 pandemic. Methods: Cross-sectional study with 60 home-nursed elderly residents and 52 community-dwelling elderly in South Jakarta. Nutritional status was determined through BMI, the risk for malnutrition was assessed by MNA, and nutritional intake was calculated using the interview method with a 24-hour food recall. Results: The study found, based on MNA, that there is a high risk of malnutrition (63.5%) among community-dwelling elderly compared to the elderly receiving home nursing (71.7%). A good prevalence of nutrition status was found in community-dwelling elderly (36.5%) better than home-nursed elderly (28.3%). Based on MNA, the elderly at risk of malnutrition who live with a home nursing are mostly male (76.5%), at 60 – 65 years (44.1%), last education is high school (38.2%), do not have disease comorbidities (70.6%), and had inadequate intake (55.9% energy, 41.2% protein, 61.8% fat, and 76.5% carbohydrate) while the elderly who live in the community are mostly female (69.4%), at 60 – 65 years (50%), the last education in elementary school (33.3%), have comorbidities (52.8%) and have inadequate intake (72.2% energy, 100% protein, 50% fat, 80.6% carbohydrate). There were significant differences in protein and fiber intake (p<0.05) between both groups. Implication: In this COVID-19 pandemic, health care workers need to be more active in conducting malnutrition risk screening particularly for community-dwelling elderly. More effort is required to advocate and ensure improved nutritional intake in this vulnerable group.